THE IMPLEMENTATION OF COMPUTER BASED TEST (CBT) AS FINAL ASSESMENT AND ITS RELEVANCE TO THE TEACHING AND LEARNING PROCESS (A case of students and teachers in SMA Negeri 1 Soe) - yabes olbata; Lesly N, Ndun (Wiralodra English Journal, 2021)
This study aims to find out the students’ and teachers’ perceptions on implementing the computer-based test as the final assessment in SMA Negeri 1 Soe. This study used a qualitative descriptive design. The instruments used were questionnaires and interviews. The data of this study was collected through spreading questionnaires and interviews. The data of this study were analyzed by using SPSS. The result of the study showed that students perceive there were some benefits of CBT implementation, such as; getting new experiences, training them to operate computers well and work harder, showing their grades directly, and teaching them to be honest. While the teachers perceive that it gave them a new challenge as the demand to be innovative to face the development of science and technology in this digital era, it was an effective way to measure the students’ learning achievement. It was a good way to promote the school level and accreditation, as an effort to improve the quality of teaching and learning, saving money because they did not need to spend it for buying papers, pens. But students and teachers also stated some weaknesses of CBT implementation such as; server error, electricity problems, time (session) delay, and computer errors.